561 - подать в виде суммы 566 - подать в виде суммы

561 - подать в виде суммы 566 - подать в виде суммы
Гость
Ответ(ы) на вопрос:
Гость
561 1)x^4(a-1)-x²(a-1)=(a-1)(x^4-x²)=x²(a-1)(x²-1)=x²(a-1)(x-1)(x+1) 2)mn(m²-1)-m(m²-1)=(mn-m)(m²-1)=m(n-1)(m-1)9m+1) 3)y²(y-1)-(y-1)=(y-1)(y²-1)=(y-1)(y-1)(y+1)=(y-1)²(y+1) 4)(2m-1)(4m²+2m+1)-6m(2m-1)=(2m-1)(4m²+2m+1-6m)= =(2m-1)(4m²-4m+1)=(2m-1)(2m-1)²=(2m-1)³ 566 1)(t-6)(t³-10t+25)=(t-6)(t-5)² 2)(m+n)(m²-mn+n²)+(m-n)²=(m-n)(m²-mn+n²+m-n) 3)(a+b)²-(x+y)²=(a+b-x-y)(a+b+x+y)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы